Therapy-resistant autoimmune nodopathy with anti-neurofascin 155 antibodies: a case report - Talers, Teodors; Pastare, Daina; Karelis, Guntis; Sankova, Eva (Frontiers in Human Neuroscience, 2024)
This study reports on a male in his late 20s, previously healthy. Symptoms started 3 months before admission to our hospital, weakness in the arms and legs, and distal hypesthesia. Primarily, the patient responded to corticosteroid therapy. As symptoms progressed, the patient received plasmapheresis and intravenous immunoglobulin therapy, with no discernible improvement. In subsequent admission, symptoms had progressed rapidly, which warranted a deeper investigation. After identifying neurofascin 155 antibodies, it was decided to start rituximab administration, as there is evidence describing its efficacy. Since then, the patient has received 3 doses of rituximab, which is partially ineffective and combined with subcutaneous immunoglobulin.